The Influence of Moisture Content and Temperature on the Long-Term Storage Stability of Freeze-Dried High Concentration Immunoglobulin G (IgG) - Arnold Duralliu; Paul Matejtschuk; Paul Stickings; Laura Hassall; Robert Tierney; Daryl R. Williams (MDPI AG, 2020)
High protein concentration products for targeted therapeutic use are often freeze-dried to enhance stability. The long-term storage stability of freeze-dried (FD) plasma-derived Immunoglobulin G (IgG) from moderate to high concentrations (10-200 mg/mL) was assessed. Monomer content, binding activity and reconstitution times were evaluated over a 12-month period under accelerated and real-term storage conditions. In the first case study it was shown that FD IgG from 10 to 200 mg/mL had minimal monomer/activity losses at up to ambient temperature after 12 months of storage. However, at 45 °C the sucrose-to-protein ratio played a significant impact on IgG stability above 50 mg/mL. All IgG concentrations witnessed moisture ingress over a 12-month period. The impact of moisture ingress from environmental exposure (between 0.1% and 5% w/w moisture) for IgG 50 mg/mL was assessed, being generated by exposing low moisture batches to an atmospheric environment for fixed time periods. Results showed that at −20 °C and 20 °C there was no significant difference in terms of monomer or antigen-binding activity losses over 6 months. However, at 45 °C, there were losses in monomer content, seemingly worse for higher moisture content samples although model binding activity indicated no losses. Finally, the difference between a low moisture product (0.1-1% w/w) and a moderately high moisture (3% w/w) product generated by alternative freeze-drying cycles, both stoppered under low oxygen headspace conditions, was evaluated. Results showed that at −20 °C and 20 °C there was no difference in terms of binding activity or monomer content. However, at 45 °C, the low moisture samples had greater monomer and binding activity losses than samples from the highest moisture cycle batch, indicating that over-drying can be an issue.